Keratin granuloma-associated giant cells in oral squamous cell carcinoma: A blessing in disguise?. (September 2022) - Sarode, Sachin C.; Sarode, Gargi S.; Sharma, Nilesh K.
Highlights: Keratin spillage-associated foreign body giant cell granuloma formation is a well-known phenomenon in cancer. Such multinucleated giant cells (MGCs) are genetically and immunologically programmed for keratin clearance. Tumor cells might also get degraded due to presence of high and low molecular weight keratin. This process can reduce the tumor burden and improves the overall prognosis. Purposeful induction of keratin granuloma formation is an interesting therapeutic opportunity in the future. Other possibilities of syncytium formation and granuloma-associated cytokines impact were also discussed. Abstract: Keratin spillage-associated foreign body giant cell granuloma formation is a well-known phenomenon in oral squamous cell carcinoma (OSCC) pathogenesis. It is mainly associated with well-differentiated grade and multi-nucleated giant cells (MGCs) with active engulfment and clearance of keratin debris from the tumor microenvironment. Although not widely investigated, these MGCs are genetically and immunologically programmed for keratin clearance. With this knowledge in mind, we propose that these programmed MGCs might also attack and degrade the tumor cells due to the presence of high and low molecular weight keratin inside the tumor cells. This process can reduce the tumor burden and improves the overall prognosis in OSCC patients. In support of this contention, an improved prognosis has been reported in OSCC patients with keratin granuloma and MGC formation. We also put forth the purposeful induction of keratin granuloma formation in well-differentiated squamous cell carcinoma as an interesting therapeutic opportunity in the future. This could be achieved through intra-lesional injection of natural or synthetic high molecular weight keratin in the stroma of OSCC tissue. Moreover, the possibility of syncytium formation with tumor cells along with granuloma-associated cytokines' impact have also been discussed in the present paper.